The Effect of Work Competency, Non-Physical Work Environment, And Work Motivation on the performance of ASN Employees in the Civil Servant Police Unit of Bandung District - Ritmasari, Kusriani Agnes; Saputro, Arie Hendra (Business Management, 2025)
This study aims to analyze the effect of job competence, non-physical work environment, and work motivation on the performance of Civil Servants (ASN) at the Civil Service Police Unit (Satpol PP) of Bandung Regency. The research employed a quantitative approach with descriptive and verification methods. Data were collected through questionnaires distributed to the entire population of ASN, totaling 44 individuals (total sampling). The results of the validity and reliability tests indicated that all research instruments were valid and reliable. Multiple linear regression analysis was used to test the hypotheses. The t-test results revealed that job competence, non-physical work environment, and work motivation each have a positive and significant influence on employee performance. The F-test results showed that the three variables simultaneously have a significant effect on employee performance. These findings highlight the importance of improving competence, creating a supportive work environment, and strengthening work motivation to optimize civil servant performance.